Investing in a Digital Marketplace for the Brick and Mortar Retail Business - Gonçalves Ferreira, João Pedro (My University, 2019)
EXECUTIVE SUMMARY Bethenga is a “isiZulu” word that means shopping. Bethenga is the name of the business venture that connects retailers with consumers, for the simple purpose of enabling a new shopping experience for consumers to digitally engage with traditional retailers, in neighbourhoods, retail parks and shopping malls. Bethenga will allow retailers to protect and grow their market share, with the idea that face to face interactions will continue to take place between people, but with the growth of the digital interchange in consumer’s lives, will require this experience to be enhanced and modernised. Bethenga will provide a platform service for retailers to advertise and sell and engage with their customers. The platform will be launched in South Africa, in Johannesburg, initially, leading to a rapid expansion to the rest of the country. This business venture was defined with trends in South Africa, and globally in mind, and was tested via a survey performed with retailers and consumers on the validity of the gap that Bethenga will operate in, and to allow for the definition of critical features the platform must have from the launch. The platform will allow retailers to compete with the online shopping providers in South Africa (Takealot, among others) and with a global footprint (for example, Amazon). The business will be launched with a lean start-up concept, to quickly add value to the market and develop in terms of features and geographic reach, when the foundation is in place. The financial projections of Bethenga indicate the business will start generating earnings from Year 2 and the main investment expenditure in Year 1 to be recouped by Year 3. The business is expected to generate around ZAR4,2M in Sales in the third year. Bethenga will own the intellectual property (IP) of the platform and will partner with numerous companies to perform non-core activities, such as advertising, logistics and payment gateways. The platform will be initially available with four subscription packages: • Online Retailer • Connected Retailer • Retailer Plus • Best Retailer For each subscription package there are specific features available, each with an incremental subscription price per offering. Consumers will register for free in the platform. The customers of Bethenga are two-fold: retailers and consumers. The retailers are the direct customers of the Bethenga platform. They are the ones that are linked to the different revenue streams the platform will generate. There is no limitation and any type of retailer can join the platform, and as much diversity will be encouraged to enable a higher product assortment for the consumer. The consumers are the indirect customers that will use the platform without having to pay a subscription. That directly will contribute to the revenue stream, linked to order value, sold by the retailers, for which a commission fee will be paid to Bethenga, based on the different subscription package the retailers will be subscribed to. The consumers will be the internet aware users within the major cities of South Africa, i.e. Johannesburg, Cape Town and Durban. Bethenga is an African start-up that has the objective to contribute to the growth of the South African Gross Domestic Product (GDP), by allowing smaller and other retailers to be digitally enabled to compete in a growing global economy.
Keywords: Retail trade -- South Africa. Business planning. Service industries -- South Africa.